Implementation of Good Governance in the Marine and Fisheries Service Office of North Sumatra - Galih Supraja; Dito Aditia Darma Nasution; Anastasia Eka Wardani; Ayunda Aulia (Pusat Riset dan Inovasi Nasional, 2023)
The problem studied in this study is, how the implementation of the principles of good governance in The Marine and Fisheries Service Office of North Sumatra with a study focus on three specific indicators, namely Transparency, Law Enforcement, and Accountability, this the researcher chose the symptoms that appear in the three These indicators are based on the results of initial observations. The main instrument used in this research is interviews with a number of informants who are considered to have the capacity to address the issues that are the focus of this study. Data processing and analysis techniques are carried out in stages: data reduction, data display, and data verification or drawing conclusions. The research results show that the three indicators are as follows: 1). In the transparency indicator so far the achievements have been relatively good, because the district always tries to provide the necessary information and data to the public or people who need it; 2) on the indicator of law enforcement as a reflection of good governance so far the achievements have been relatively good although not yet optimal, especially in terms of increasing employee discipline which is still experiencing maximum improvement specifically in terms of activity in the office; 3) the accountability indicators so far have been going quite well, the thing that is of particular concern to this indicator is the timeliness in compiling and submitting accountability reports from employees to the leadership which sometimes still experience delays.